INTERNET ADDICTION IN CHILDREN - Hestin Oktiani; Eka Yuda Gunawibawa (Metakom, 2020)
The growth of Indonesian internet users is very fast, including internet users between the ages of 10-12 years who are still in the category of children's internet users. One of the impacts of the growth of internet users on children is media add. So that these children can access shows and content on the internet, which are less educational and not suitable for children. This research is a type of descriptive research or a description of a phenomenon with a quantitative approach. This study also sought to find a causal relationship (casuality) from 250 respondents in 5 schools in Bandarlampung.